Agency cost and long run performance of debt issuers - Ibrahim, Yusnidah; Uddin, Md Mohan; Taufil Mohd, Kamarun Nisham; Minai, Mohd Sobri (2011)
This study focuses on the agency costsexplanation of long run performance of debt issuers based on debt issuance data in Malaysia during January 2001 to October 2009.Long run performance is measured (BHAR) while growth opportunity (GO), ownership concentration (OC) and free cash flow (FCF) are adopted as the proxy for agency costs.Using linear regression method, the study finds that BHAR is positively influenced by GO and OC and negatively influenced by FCF which support the agency cost explanation of capital structure. Increase inthe performance of debt issuersis found to be associated with the monitoring role of debt. Debt issuers with more concentrated ownership are found to be benefitted from the issuancethrough the reduction of agency costs.